2012
DOI: 10.3727/096368911x600957
|View full text |Cite
|
Sign up to set email alerts
|

Altered Oxygen Metabolism Associated to Neurogenesis of Induced Pluripotent Stem Cells Derived from a Schizophrenic Patient

Abstract: Schizophrenia has been defined as a neurodevelopmental disease that causes changes in the process of thoughts, perceptions, and emotions, usually leading to a mental deterioration and affective blunting. Studies have shown altered cell respiration and oxidative stress response in schizophrenia; however, most of the knowledge has been acquired from postmortem brain analyses or from nonneural cells. Here we describe that neural cells, derived from induced pluripotent stem cells generated from skin fibroblasts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(55 citation statements)
references
References 53 publications
5
49
0
1
Order By: Relevance
“…To induce embryonic stem cells to direct neural differentiation, we performed an adaptation of Baharvand et al (2007) protocol (Paulsen et al, 2012). Briefly, 70% confluent BR1 culture was differentiated to the neural lineage in defined adherent culture by retinoic acid and basic fibroblast growth factor (bFGF) within 18 days of culture.…”
Section: Methodsmentioning
confidence: 99%
“…To induce embryonic stem cells to direct neural differentiation, we performed an adaptation of Baharvand et al (2007) protocol (Paulsen et al, 2012). Briefly, 70% confluent BR1 culture was differentiated to the neural lineage in defined adherent culture by retinoic acid and basic fibroblast growth factor (bFGF) within 18 days of culture.…”
Section: Methodsmentioning
confidence: 99%
“…As far as we are aware, only a few studies utilized iPS cells in schizophrenia research. Nonetheless, two exploratory studies have already suggested involvement of oxidative stress: one case report indicated an increase in reactive oxygen species in SZ [26]. Another group showed that SZ-derived iPS cells had difficulty of differentiating to neurons and exhibited substantial mitochondrial deficits [16**].…”
Section: Biochemical Evidence In Human Biospecimensmentioning
confidence: 99%
“…Accordingly, altered oxygen metabolism has been associated to the neurogenesis of iPSCs derived from a schizophrenic patient [111]. Although future studies are warranted to address the connection between neural differentiation and mitochondrial function in schizophrenia, the studies so far conducted highlight the potential that iPSC-based studies may bring to the dissection of the molecular mechanisms underlying complex psychiatric disorders.…”
Section: Mitochondrial Impairment In Ipsc Models Of Brain Disordersmentioning
confidence: 99%